Characterization of Surface Runoff Pathways and Erosion Using Hydrological Attributes Under Simulated Rainfall - Zhang, Lichao; Liu, Xiaojun; Song, Yuejun; Li, Jun; Cai, Chongfa; Zhao, Xiaomin; Li, Zhaoxia (Frontiers in Earth Science, 2021)
This study aimed to explore the feasibility of applying hydrological attributes to characterize surface runoff pathways in the process of hillslope soil erosion due to rainfall. Combined with sub-millimeter high-resolution laser scanning and computer digital image processing method, three hydrological indicators (i.e., sinuosity, gradient, and orientation) were used to investigate the changes of the surface runoff pathways on the slope of three typical southern red soils (i.e., shale (HS), and Quaternary red clay soils (HQ1 and HQ2) under simulated rainfall conditions). The results indicated that the sinuosity and orientation of the three red soils under the rainfall intensity of 1 mm/min and 2 mm/min showed an overall downward trend within the intervals of 0.82%-9.45% and 5.60%-31.44%, respectively. The gradient increased with the accumulation of rainfall and tended to be close to the slope of the test plot. Continuous rainfall increased the differentiation in runoff pathway characteristics and the greatest changes appeared at the first rainfall. Compared with HS and HQ1, the runoff pathway characteristics of HQ2 changed more consistent. Specifically the sinuosity of the first-level had the most dramatic change with the progress of rainfall. The rainfall intensities had a significant impact on the correlation between indicators. The correlation coefficients sorting with surface roughness were orientation >gradient >sinuosity. And they were significantly related to runoff under 1 mm/min rainfall intensity, while had positive correlation with sediment under 2mm/min rainfall intensity. In conclusion, there were more remarkable relationship between orientation, gradient and slope erosion under 1 mm/min rainfall intensity. This provided innovative ideas for applying the orientation and gradient to the simulation and prediction model of the rainfall erosion process in the sloping farmland in the southern red soil area.